Gender Representation in Indonesian EFL Textbooks English for Nusantara - Elsa Uki Widiyanto; Lintang Ratri Rahmiaji (Soegijapranata Catholic University, 2026)
The study attempts to show the gender representation in eight-grade EFL textbook entitled “English for Nusantara” published by the Indonesian Ministry of Education and Culture. Referring to Porreca’s framework (1984) concerning gender representation in textbook, this study elaborates the omission, firstness, occupational role, masculine generic construction, adjective usage, and gender activities in Indonesian EFL textbook. This research utilizes qualitative approach through the secondary data as the main data were obtained from English textbook by considering the occurrence of male and female characters in the textbook. The results showed that male characters dominate in illustrations and text compared to female. Besides, male characters are attributed with adjectives and gender activities which emphasize competence, strength, dominance, and leadership whereas females are attributed with nurturing, emotions, and physical attractiveness.